PRAKTIK BERORIENTASI SOFT SKILLS DENGAN PENDEKATAN INDUSTRIAL CULTURE BASED GEMBA KAIZEN MODEL - Edi Siregar; Walan Yudiani (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2020)
The research objective is to design learning model with orientation capability increase student soft skills. The data collection method used observation, tests and self-assessment. While data analysis using bar charts, check sheets and line charts. Based on the results of data analysis there are several important findings include that the implementation of practice learning through project-based learning approach based industrial culture Gemba Kaizen model of the first cycle and cycle II and III provide a positive response to the formation of students soft skills evidenced by the increase in soft skills mastery significantly with the result that more dominant on communication skills and report writing skills then successively on professional and problem solving skills, personal quality and teamwork skills.